Redox Active Molecules in Cancer Treatments - Stepanić, Višnja; Kučerová-Chlupáčová, Marta (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The book is a reprint of a Special Issue with the same title published online in the chemical journal Molecules (ISSN 1420-3049) within the section of Medicinal Chemistry. It was edited by academic guest editors from September 2020 to April 2022. In total, it includes eighteen research/review articles including the editorial.